107 EMERGENCY DEPARTMENT IN THE HOME, WHO IS THE EDITH PATIENT?. (18th November 2021) - Davis, A J; Doyle, C; Delaney, A; Sweeney, A; Nally, S M; Namara, R M
Abstract: Background: The EDITH team has provided an alternative care pathway for older adults in need of emergency services. This vulnerable patient population receive emergency medical and occupational therapy treatment and intervention in their home environment. The typical patient profile is assumed to be 'frail older adults', but this needs to be more specifically defined within the clinical practice in EDITH. Methods: A total of 230 electronic patient records were selected at random. Data was audited and analysed with regard to clinical descriptors for this patient population. Results: Of the 230 patients treated, 26 were referred to hospital or rehabilitation facilities. This is a conveyance rate of 11% which is above the average rate of 7.2% for this service. The Rockwood Clinical Frailty Scale (CFS): 22% had a CFS of 5 (mildly frail), 37% had a CFS of 6 (moderately frail), 22% had a CFS of 7 (severely frail), 3% had a CFS of 8 (very severely frail). Living Status : 26% living alone, 48% living with family, 4% sheltered living accommodation and 22% in nursing homes. Formal Supports : 37% have no formal supports, 18% have <10 hours per week, 19% have between 11–21 hours, 4% have 24-hour care and 22% reside in nursing homes. Presenting complaint : 41% medically unwell, 23% fall, 14% functional decline, 9% pain, 5% infection, 5% orthopaedic and 2% confusion. Ages range from 61 years to 100 years with an average age of 82 years. Conclusion: It is imperative to identify the type of patient that uses this service, in order to plan for future service needs and ensure their current clinical care needs are being met. Of note, a significant proportion of patients are living alone, have high CFS scores and have no formal supports in situ.